Towards a Hopeful University - Ciżewska-Martyńska, Elżbieta (Stan Rzeczy, 2024)
Drawing on insights from sociology and psychology, this paper points at hope as one of the key personal and communal strengths that contemporary academia needs in order to make use of its potential and fulfil its unique mission. It also shows the connection between futures studies, sociological reflection on hope, and the sociological understanding of leadership. The difference between unwarranted optimism and hope is explained, and hope is presented as a deeply creative, active process involving thinking more than feeling. The author argues that modern universities pay too little attention to the positive aspects of life, and thus universities become paradoxically less capable of executing their mission: to be leaders of positive change in every dimension of life, to conduct free research and free debate in which every bit of truth is respected, and to form ethical, wise leaders. Sadly, some fields of knowledge, such as sociology, lack a sufficiently developed theoretical apparatus to confront the problem. This paper concludes with recommendations for Eastern European academia.